Implementation Of Human Resource Management At Yusro Hotel Restaurant And Convention Jombang - Leksono, Agung Budi; Alifah, Humairoh Nur (Journal Research of Social Science, Economics, and Management, 2021)
This study aims to determine the implementation of the HRM operational function (particularly in terms of procurement, training and development, integration, compensation, maintenance, discipline, and employee termination), the obstacles that hinder the successful implementation of the HRM operational function, as well as to recommend alternative strategies in overcoming the problem. related to HR at Hotel Yusro Jombang. The approach used in this research is a qualitative approach which is analyzed using an interactive analysis model and combined with a SWOT analysis technique, then tested using a source triangulation technique. The results showed that the implementation of HRM at Yusro Hotel could not be said to be effective because the functions of employee procurement, employee development, employee integration, employee maintenance, and employee discipline had not been implemented optimally. Barriers that occur during the implementation process of human resource management at Hotel Yusro Jombang are divided into two types, namely revenue and management incompetence in planning various HR management programs. And from the results of calculations and analysis on the Cartesian SWOT diagram, it shows that the position of the implementation of human resource management at the Yusro Hotel Jombang is in quadrant III, so the strategy that can be used to overcome HR problems at the Yusro Hotel is the WO strategy, namely by holding employee team building, reviewing re-employment process, realization of the competency certification program, and promotion of products and services through various means.